Between Original Meaning and Social Mobilization: The Case of the Second Amendment to the U.S. Constitution (Universidad de San Andres Law Review, 2021)
In this paper I intend to explore the emergence of the right to kee´p and bear arms in the American legal system. Taking into consideration the origins of the Second Amendment to the US Constitution and the intentions behind its adoption, I argue that the fact that it is commonly read as a right of that nature does not obey a faithful interpretation of the original meaning of the constitutional text, but rather of decades of social mobilization that, in coordination with political actors, succeeded in reinterpreting its meaning.
Keywords: Second Amendment; gun rights; social movement; constitutional interpretation; originalism; popular constitutionalism; strategic litigation